Peran Desain Pembelajaran Dalam Pengembangan Moral Anak Didik - Rusydi Syadzili, Muhamad Fatih (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
This article explore moral education, learning system based on educational institutions. Students have different style from each other, so moral development in the design of learning is very important for teachers. Cause the development of learning design is related to studentsâ€™ morals, sudent be able to become a make changes as a whole, and bring changes to individual students.The design of moral learning is a system for the development of education and training programs. This learning system will make students have good morals in the bad behavior on society. Learning system must make teacher be a good person, cause learning system must make actual learning, not only focused on the substance of teaching material, but more strived to internalize the values   of the teaching material.